Effects of a Gluco-oligosaccharide on Growth Performance of Nursery Pigs - F. Wu; M. D. Tokach; J. M. DeRouchey; S. S. Dritz; J. C. Woodworth; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 3,456 nursery pigs (PIC L337 × 1050, initially 12.4 lb BW) were housed in 3 commercial research rooms and used in a 42-d growth study to determine the effects of gluco-oligosaccharide (Midori USA, Inc., Cambridge, MA) on growth performance. In each room, pens of pigs (27 pigs/pen) were blocked (6, 5, and 5 blocks in rooms 1, 2, and 3, respectively) by initial pen BW. Within blocks, pens were allotted randomly to 1 of 8 dietary treatments in a 2-phase feeding program (d 0 to 14 and d 14 to 42). Dietary treatments were arranged in a 2 × 3 factorial, with or without antibiotic (0 or 55 ppm, Carbadox, Phibro Pro, Teaneck, NJ) and 4 concentrations of gluco-oligosaccharide (0, 200, 400, and 600 ppm). Gluco-oligosaccharide product used in rooms 1 and 2 originated from a different batch than that used in room 3. For the overall feeding period, no room × antibiotic × gluco-oligosaccharide or antibiotic × glucooligosaccharide interactions were observed for any growth responses, but tendencies were found (P<0.10) for room × gluco-oligosaccharide interaction for final BW and ADG. In rooms 1 and 2, antibiotic treatment increased ADG and ADFI in all feeding periods and improved F/G from d 14 to 28 and d 28 to 42. Increasing gluco-oligosaccharide improved (linear, P<0.05) ADG and F/G from d 0 to 14. It also increased (P = 0.047) ADG and tended (P = 0.087) to increase ADFI from d 14 to 28, but did not alter the growth responses from d 28 to 42. For the overall period (d 0 to 42), adding an antibiotic to the diet increased (P<0.01) ADG and ADFI, but did not affect F/G. Increasing gluco-oligosaccharide improved (linear, P<0.01) ADG and F/G and tended (P = 0.063) to linearly increase ADFI. In room 3, a much smaller response was observed for antibiotic inclusion with only improved (P = 0.005) F/G from d 14 to 28 and increased (P<0.05) ADG and ADFI from d 28 to 42. Pigs fed increasing glucooligosaccharide tended (linear, P<0.10) to have reduced ADG and ADFI; however, the overall growth performance was not affected by antibiotic or gluco-oligosaccharide treatments. In conclusion, feeding gluco-oligosaccharide may improve growth performance in nursery pigs, and this effect appears to be independent of the use of antibiotic and more prominent during the early nursery phase. However, due to some room × gluco-oligosaccharide interactions, further research is required to confirm the consistency of the responses to the gluco-oligosaccharide used in this study.
Keywords: antibiotic; gluco-oligosaccharide; growth; nursery pig